Effects of phosphorus content on fatigue performance of friction stir welded mild steels. (21st March 2022) - Wang, Yixun; Tsutsumi, Seiichiro; Kawakubo, Takumi; Fujii, Hidetoshi
Highlights: Anti-corrosion performance is proportional to fatigue strength of FSW joints. Increasing phosphorus content enhances fatigue strength of FSW joints. Longer weld defect due to inadequate downward load result in shorter fatigue life. Weld defect has barely no influence on ductile strength. Abstract: The weathering steels for bridge construction joined by fusion welding often suffer from the hot cracks due to the phosphorus segregation. The present study assessed the fatigue performance of newly developed weathering steels with high phosphorus content joined by friction stir welding (FSW) below A1 temperature, by which the heat affected zone (HAZ) softening and weld defects were successfully inhibited. The fatigue life of the FSW joints of three mild steels was evaluated and compared to the design curve. The accumulation of plastic deformation in different regions was analysed and various ratcheting behaviors were studied. The influence of weld defects on the fatigue life due to the inadequate downward loading was also classified. The results showed that the fatigue strength of three mild steels was much higher than the FAT112 design curve, and the S-N curves were extremely flat. The base metal region of the FSW specimens where the fracture usually occurred illustrated a larger accumulation of plastic deformation than the weld nugget. The fatigue fracture at the weld nugget was induced by weld defects and the fatigue life was decreased by as long as 14.7 times.